PEMBINAAN TES POTENSI AKADEMIK BAGI GURU DAN SISWA SMA INDERALAYA - Herlina Hanum (Lembaga Pengabdian pada Masyarakat, 2020)
Academic potential test (TPA, GRE) is one of the test items used for selection, both for university admission and employee recruitment in various agencies. One group of people who are very likely to take TPA is high school students. Since TPA is not included in the final national examination (UAN), high school students pay less attention to their mastery of the TPA. In order to help them, coaching is needed to be done to provide understanding and mastery in solving TPA question effectively. The participation of teachers in this training is intended to sustain the results of the activities as they will be able to foster students of the next generation. The training was held at PGRI Inderalaya High School. There are 29 participants consisting of 7 teachers and 22 students of Class 12. Participants were guided to recognize, understand, and analyze each form of questions. Then the method of solving problems effectively is discussed. The types of questions that are discussed are verbal, series, logic, and images. Based on the pretest and posttest with the same questions, it was significantly concluded that participants were able to absorb the training material and use it at the posttest.